Analisis Kesantunan Berbahasa Siswa dalam Berinteraksi pada Proses Pembelajaran Bahasa Indonesia - Meilita Rizkia Dwi Nanda; Dedi Riyan Rizaldi; Mahsun; Novi Sarianti; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2024)
Language is a means of communication between humans and others. When communicating, it is necessary to pay attention to several factors, one of which is politeness in language. The purpose of this study was to analyze students' politeness in interacting during the Indonesian language learning process in class. This study used a qualitative method with data collection techniques using observation, interview, and documentation techniques. The data obtained were analyzed descriptively to describe various findings during the study. Based on the data analysis process and discussion, it was concluded that students' politeness in language adhered more to the principles of the maxims of tact, simplicity, agreement, appreciation, and sympathy